A framework for surface profile optimization in sinker-edm via response surface methodology - Rohman, Rohman; Sukarman, Sukarman; Ulhakim, Muhamad Taufik; Supriyanto, Danang (Politeknik Negeri Lhokseumawe, 2025)
Sinker Electrical Discharge Machining (SEDM) is a powerful technique used for shaping hard materials and creating complex designs. SEDM effectively machines hardened steel, titanium, and tungsten carbide, materials challenging for conventional methods. This study aims to identify the optimal surface profile (Ra) as a response variable in the SEDM process. This study utilized hardened SKD11 as the workpiece and graphite as the electrode, employing Response Surface Methodology (RSM) for optimization. The investigation focused on the pulse current, spark-on time, and gap voltage as the input parameters. The findings revealed that Sample 7 achieved the smoothest surface (at Ra = 10 µm), while Sample 13 had the roughest (at Ra = 20 µm). The analysis of these results determined the ideal conditions for the pulse current at level 1, spark-on time at level 3, and gap voltage at level 3, resulting in a surface profile of 10.2 microns. The successful application of RSM optimization in SEDM significantly contributes to the precision machining of alloy steels, which plays a crucial role in material-processing operations.